Evaluation of some composite paint coatings' appearance quality using fractal dimension - Loganina, Valentina; Fediuk, Roman; Lesovik, Valery; Amran, Mugahed; Qader, Diyar N.; Litvinets, Olga; Okhotkina, Viktoria; Rashid, Raizal S. M.; Lomov,, Maksim; Moskovaya, Irina (Multidisciplinary Digital Publishing Institute, 2023)
Composite materials are characterized by multiple layers, which leads to a complexity in the design in order to ensure the effective operation of the constituent elements. This article provides information on the use of fractal dimension in assessing the quality of the appearance of paint coatings. The scientific originality of the article lies in the establishment of a correlation between the surface roughness of coatings, the quality grade of their appearance and fractal dimension. As a result, a model of the length of the coating surface profile, with the fractal dimension D, was proposed. The practical significance lies in the proposal to evaluate the quality of the surface of paint and varnish coatings in terms of fractal dimension. An increase in the surface roughness of the coating, a decrease in the appearance quality grade and an increase in the fractal dimension have been observed. Numerical values of the index of the fractal dimension of the coating surface profile, which depended on the porosity of the substrate, have been obtained. The influence of the filling of the paint composition on the quality of the appearance of the coatings has been estimated. It has been revealed that there was an increase in the surface tension of the paint composition, a decrease in the quality of the appearance of the resulting coating and an increase in the roughness and fractal dimension of the coating surface. The influence of the method of applying the paint composition and the preparation of the base surface on the quality of the appearance of the coatings are considered. The results obtained can be applied in various types of production to improve the quality of paint coatings.